Cryopreservation of water-based suspensions by the floating process for blood storage - Khayyat, Diaa; Rittinghaus, Tim; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):297